2015
DOI: 10.1371/journal.pone.0125237
|View full text |Cite
|
Sign up to set email alerts
|

Deceptive Intentions: Can Cues to Deception Be Measured before a Lie Is Even Stated?

Abstract: Can deceitful intentions be discriminated from truthful ones? Previous work consistently demonstrated that deceiving others is accompanied by nervousness/stress and cognitive load. Both are related to increased sympathetic nervous system (SNS) activity. We hypothesized that SNS activity already rises during intentions to lie and, consequently, cues to deception can be detected before stating an actual lie. In two experiments, controlling for prospective memory, we monitored SNS activity during lying, truth tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 68 publications
7
21
0
2
Order By: Relevance
“…That is, in the more experimental studies of Ströfer et al (2015) participants did not commit a transgression, questions were contently unrelated, and neither had personal relevance nor were embedded in an interactive interview.…”
Section: Discussionmentioning
confidence: 99%
“…That is, in the more experimental studies of Ströfer et al (2015) participants did not commit a transgression, questions were contently unrelated, and neither had personal relevance nor were embedded in an interactive interview.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the time intervals (epochs) from which the EDA signal was used to extract features for associated events were determined. This process was motivated by the work of [54] that demonstrates that the cues in EDA are present before the event of interest. The segmentation procedure for various types of epochs follows.…”
Section: Data Segmentation and Annotationmentioning
confidence: 99%
“…EDA can be also used as an indicator of deceit since lying costs more mental effort than telling the truth [58] and the cognitive load activates SNS [13,38]. Previous research [36,54] found increased EDA for lying as compared to truth-telling. Moreover, EDA is an autonomic-based physiological response which makes it hard to control and therefore less susceptible to strategic manipulations [18], and is a good indicator of deceit.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the polygraph [12] has shown that several physiological parameters can be correlated with deception, with various degrees of accuracy. We can distinguish between invasive measurement techniques, used to measure parameters such as the galvanic skin response (GSR) (or other measurements of the electro-dermal activity) [12][13] [14], heart rate and blood pressure [12] [15], respiratory rate [12] or brain activity [16] [17] and noninvasive measurement techniques, that can be used to monitor heart rate, using Fast Fourier Transform (FFT) video analysis [8] [18], respiratory rate (FFT video analysis) [19] [20], voice audio frequencies [21] [22], facial expressions [22], or eye movements and blink rates [23][24] [28].…”
Section: Deception and Its Physiological Manifestationsmentioning
confidence: 99%